Exploring Educators' Environmental Education Attitudes and Efficacy: Insights Gleaned from a Texas Wetland Academy. Issue 3 (2nd July 2016) - Nesmith, Suzanne M.; Wynveen, Christopher J.; Dixon, Erin M.; Brooks, Bryan W.; Matson, Cole W.; Hockaday, William C.; Schaum, Megan A.; DeFillipo, John E.
Abstract : It has been determined that some 60% of wetlands worldwide have been destroyed in the last 100 years, and, for more than a decade, researchers have warned of a global freshwater imperative. In the context of these environmental deteriorations and ecological crises, teaching about environmental issues and ways to preserve the world's environment has become increasingly important at both national and international levels. Additionally, these issues highlight the necessity of developing wetland centers and determining a means for building understanding of wetlands, water conservation, and water reuse. This study investigated the impact of an onsite wetland environmental education (EE) experience on educators' attitudes and efficacy. Participants were 13 selected educators currently teaching elementary, middle school, and high school level students. Pre- and post-experience data were collected through an environmental teaching perceptions instrument [Ko, A., & Lee, J. C. (2003). Teachers' perceptions of teaching environmental issues within the science curriculum: A Hong Kong perspective. Journal of Science Education and Technology, 12 (3), 187–204] and a 12-month post-experience focus group interview. Results suggested that the experience did not significantly impact the educators' attitudes but did impact their EE efficacy; specifically, the educators' indicated enhanced self-efficacy in teaching EE and heightened perceptions of their abilities to incorporate teaching practices that would positively change students' EE knowledge, attitudes, and skills. The significant, positive, sustained changes in participants' efficacy were attributed to the distinctive design of the workshop; an inquiry-based research experience situated within a specific context (a 1, 840-acre constructed wetland system) and addressing water reclamation and reuse with a targeted group of educators who have a personal investment in these topics.